Exercise testing and training in people with Huntington's disease. (February 2015) - Dawes, H; Collett, J; Debono, K; Quinn, L; Jones, K; Kelson, MJ; Simpson, SA; Playle, R; Backx, K; Wasley, D; Nemeth, AH; Rosser, A; et al.
Objective: To explore exercise response in people with Huntington's disease (HD). Design: Experimental observational study with a randomly allocated subgroup before/after interventional study. Setting: Community. Subjects: People with HD ( n =30) and a healthy comparator group ( n =20). Thirteen people from the HD group were randomly allocated to an exercise training program. Main measures: Heart rate (HR) and perceived exertion on the Borg-CR10 scale (RPE) during a submaximal cycle ergometer exercise test (three minute unloaded and nine minute 65%-75%HRmaximum phase). Expired air and lactate measures were available for 8 people with HD during the exercise. Intervention: A 12 week gym and home walking exercise programme ( n =13). Results: People with HD achieved a lower work rate at nine minutes (82±42(0-195) v 107±35(50 -185) Watts ( p <0.05)), but higher RPE at both three (3±2(0-7) v 1±1(0-4)) and nine minutes (7±3(1-10) v 5± 2(2-9)) both p <0.01, compared to the healthy group and did not achieve a steady state HR during unloaded cycling. People with HD also demonstrated higher than expected lactate at three 2.5±2.5(1.1-8)mmo.L-1 and nine 3.8±1.9(1.2-6.6)mmo.L-1 minutes and respiratory exchange ratio at three 0.78±0.03 (0.74-0.81) and nine minutes 0.94±0.11(0.81-1.15). After exercise training there were no changes observed in HR or RPE responses during the exercise test. Conclusions: There was a large variability in the observed metabolic and physiological responses to exercise in people with HD. The observed exercise responses suggest that altered exercise prescription parameters may be required for people with HD and that exercise response and factors' affecting this requires further investigation.